Indications for Caesarean Section for women of low obstetric risk - an audit - Murete Sanare Lukumay; Jane Kokushubila Muzo; Amani Idris Kikula; Peter Joseph Wangwe; Andrea Barnabas Pembe (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2023)
Introduction: The Caesarean Section (CS) rate is dramatically increasing across obstetric populations. This study aimed to determine the adherence to criteria for standard diagnosis of the common indications for CS among women of a low-risk group. This group, known as group 3 in the Robson classification, is multiparous, term with singleton pregnancy and have not had a previous CS. Methods: We conducted a cross-sectional study at Muhimbili National Hospital from August to December 2018. The criteria for standard diagnosis of foetal distress, obstructed labour, arrested labour and cephalopelvic disproportion were adopted from peer groups publications based on local expert consensus. Data were analysed using a statistical package for social sciences (SPSS) version 20. Results: A total of 1,670 emergency CS's were performed during the study period, 392 (23.5%) were women of Robson group 3, of these women 101 (25.8%) had foetal distress, 92 (23.5%) obstructed labour, 88 (22.4%) arrested labour and 64 (16.4%) cephalopelvic disproportion. The proportion of CS's which met the criteria for standard diagnosis of indications for CS were 61.4% foetal distress, 52.2% obstructed labour, 58% arrested labour, and 45.3% CPD with total average of 55.1%. Conclusion: Generally, the standard criteria for audited indications of CS have been met by 55.1% during the study period. Thus, follow up, on the job training and updating about adherence to standard criteria for best practice are recommended.